A controlled trial to investigate whether the orientation of the bevel and angle of approach determine the side of endobronchial intubation in an adult manikin. Issue 3 (March 2020) - Dawson, SR; McConaghy, PM; Barr, RC
One of the commonest complications of endotracheal intubation occurs when the tip of the endotracheal tube passes distal to the carina and enters one of the main bronchi. The perioperative practitioner may observe high airway pressures, hypoxia or even pneumothorax. The most common reason given for the high incidence of right endobronchial intubation is that the right main bronchus comes off the trachea at a more acute angle from the midline. We sought, however, to explore two other factors which may explain this phenomenon – the angle of the tube's bevel and its trajectory of approach. We conducted a prospective controlled trial in which doctors from our department intubated the trachea of an adult manikin in three distinct sets using standard tube, reversed tubes and reversed laryngoscope blades. We found that the angle of the bevel and trajectory of approach determines the side of endobronchial intubation in an adult manikin.